DIGITAL ECONOMY AS A NEW STAGE OF GLOBALIZATION - G. G. Goloventchik (Цифровая трансформация)
The purpose of the article is to show the influence of modern information technologies on the processes of globalization. The article shows how the digital transformation of society under the influence of the explosive growth of cross-border data led to the next stage of globalization, a characteristic feature of which is a new form of organization of economic relations — the digital economy. The essence of globalization, its features, stages and tendencies are considered. The advantages provided by the development of modern information and communication technologies (especially the Internet) to participants in the processes of globalization are reflected. The characteristic of the digital economy as a new stage of economic development is presented, its various definitions and specific features are considered. The specifics of the development of cross-border electronic commerce, its advantages and the essence of the cryptocurrency as potential new world money are described. Considerable attention is paid to the trends in the development of new global digital processes and the risks generated by the digital economy.